Genetic diversity and its association with heterosis in rice (Oryza sativa L.) - Hossain, K; Akter, A; Begum, H; Khatun, M; Masuduzzaman, ASM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 39-46